2004
DOI: 10.1074/jbc.m405945200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Serum Response Factor Cofactor in Cardiac Gene Regulation

Abstract: The transcription factor serum response factor (SRF) plays an important role in the regulation of a variety of cardiac genes during development and during adult aging. A novel SRF cofactor, herein called p49/STRAP, for SRF-dependent transcription regulation-associated protein, was recently identified in our laboratory. This protein interacted mainly with the transcriptional activation domain of the SRF protein and was found to bind to SRF or to the complex of SRF and another cofactor, such as myocardin or Nkx2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 44 publications
1
64
0
Order By: Relevance
“…Both factors have the possibility of acting as positive or negative regulators when they bind to DNA, which is dependent of the recruitment of positive or negative transcriptional co-regulators. In recent years the myocardin family of transcription factors, especially myocardin-related transcription factors A/B, have been associated with the regulation of cardiac genes (43)(44)(45)(46), by interactions with the SRF, potentiating the effect of these factors. Thus, it is possible that some of these cofactors contribute with SRF to regulate expression of the casq2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Both factors have the possibility of acting as positive or negative regulators when they bind to DNA, which is dependent of the recruitment of positive or negative transcriptional co-regulators. In recent years the myocardin family of transcription factors, especially myocardin-related transcription factors A/B, have been associated with the regulation of cardiac genes (43)(44)(45)(46), by interactions with the SRF, potentiating the effect of these factors. Thus, it is possible that some of these cofactors contribute with SRF to regulate expression of the casq2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Transient transfections were carried out with the Lipofectamine and Plus reagents (Invitrogen, Carlsbad, CA) as previously described (Zhang et al, 2001;Zhang et al, 2004). Briefly, at 4 h after the transfection was initiated, the NIH3T3 cells were placed in Dulbecco's modified Eagle's medium with 10% fetal calf serum and incubated overnight.…”
Section: Transfection Assaysmentioning
confidence: 99%
“…The protein p49/STRAP was identified in our laboratory in search of proteins that regulate cytoskeletal genes related to cardiac function [1]. Our initial observations indicated that p49/STRAP is a cofactor of serum response factor (SRF), contributing to the regulation of SRF target genes.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions likely modulate SRF function and may also enable SRF to mediate tissue-specific regulation of its target genes at different developmental stages [6,7]. A model of transcriptional regulation by SRF and its binding proteins has been proposed, in which the interaction of multiple proteins (including p49/STRAP) affects the outcome of the expression of SRF target genes [1]. SRF has two functional domains.…”
Section: Introductionmentioning
confidence: 99%